2013
DOI: 10.1371/journal.pone.0079276
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Anopheles Mosquito Population Dynamics and the Potential for Malaria Transmission

Abstract: The parasites that cause malaria depend on Anopheles mosquitoes for transmission; because of this, mosquito population dynamics are a key determinant of malaria risk. Development and survival rates of both the Anopheles mosquitoes and the Plasmodium parasites that cause malaria depend on temperature, making this a potential driver of mosquito population dynamics and malaria transmission. We developed a temperature-dependent, stage-structured delayed differential equation model to better understand how climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
239
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(258 citation statements)
references
References 50 publications
14
239
2
3
Order By: Relevance
“…Work showing that cuticular hydrocarbon amount and composition can change substantially with circumstances in Anopheles mosquitoes (Caputo et al, 2005;Reidenbach et al, 2014;Wagoner et al, 2014) bears out this idea. Irrespective of its cause, including age-related variation in tolerance of abiotic conditions is important for improving mechanistic models of population dynamics in mosquitoes (Styer et al, 2007;Beck-Johnson et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…Work showing that cuticular hydrocarbon amount and composition can change substantially with circumstances in Anopheles mosquitoes (Caputo et al, 2005;Reidenbach et al, 2014;Wagoner et al, 2014) bears out this idea. Irrespective of its cause, including age-related variation in tolerance of abiotic conditions is important for improving mechanistic models of population dynamics in mosquitoes (Styer et al, 2007;Beck-Johnson et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…A negative correlation indicated that mosquito abundance is high when DRT is low (SW Monsoon) and vice versa. Impacts of temperature on population dynamics and vector competence are complex (Beck-Johnson et al, 2013). Mosquitoes are sensitive to temperature throughout their life cycle and it has been shown by mathematical modeling studies that the fluctuations in diurnal temperatures may affect the mosquito life cycle and malaria transmission (Beck-Johnson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are no data on dengue cases available from the hospital. However, the temperature ranges of the peak transmission of malaria and dengue are overlapping [mid 20's ºC for malaria, per (Beck-Johnson et al 2013); 23-34ºC for DENV, per (Mordecai et al 2017)]. Therefore, we expect that the transmission patterns would be similar.…”
Section: Diana Valenciamentioning
confidence: 99%
“…Therefore, we expect that the transmission patterns would be similar. Beck-Johnson, L. M., et al (2013). "The effect of temperature on Anopheles mosquito population dynamics and the potential for malaria transmission."…”
Section: >>> Mosquito Species Are Quite Variable In Their Feeding Habmentioning
confidence: 99%